Genetic history of the African Sahelian populations. (16th January 2018) - Černý, V.; Kulichová, I.; Poloni, E. S.; Nunes, J. M.; Pereira, L.; Mayor, A.; Sanchez‐Mazas, A.
Abstract : From a biogeographic perspective, Africa is subdivided into distinct horizontal belts. Human populations living along the Sahel/Savannah belt south of the Sahara desert have often been overshadowed by extensive studies focusing on other African populations such as hunter‐gatherers or Bantu in particular. However, the Sahel together with the Savannah bordering it in the south is a challenging region where people had and still have to cope with harsh climatic conditions and show resilient behaviours. Besides exponentially growing urban populations, several local groups leading various lifestyles and speaking languages belonging to three main linguistic families still live in rural localities across that region today. Thanks to several years of consistent population sampling throughout this area, the genetic history of the African Sahelian populations has been largely reconstructed and a deeper knowledge has been acquired regarding their adaptation to peculiar environments and/or subsistence modes. Distinct exposures to pathogens—in particular, malaria—likely contributed to their genetic differentiation for HLA genes. In addition, although food‐producing strategies spread within the Sahel/Savannah belt relatively recently, during the last five millennia according to recent archaeological and archaeobotanical studies, remarkable amounts of genetic differences are also observed between sedentary farmers and more mobile pastoralists at multiple neutral and selected loci, reflecting both demographic effects and genetic adaptations to distinct cultural traits, such as dietary habits.